A rhetoric of meanings : exploring the frontiers of language usage - Apostolova, Gergana (Cambridge Scholars Publishing, 2015)
This book presents an in-depth analysis of language's role as the tool and environment for human survival on Earth, examining its ability to provide an unlimited space for telling individual stories that bear the knowledge of mankind's self-significance. The book is the result of a 20-year-long composite study of language phenomenology grounded in the interactions of Bulgarian and English, approached in a game-like fashion where the play with language units transcends levels of meanings based on significances, and explored through the four basic avatars of activated language: the learner, the.